2023
DOI: 10.3389/fcvm.2023.1038738
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers and hotspots evolution in anti-inflammatory studies for coronary heart disease: A bibliometric analysis of 1990–2022

Abstract: BackgroundCoronary heart disease (CHD) is characterized by forming of arterial plaques composed mainly of lipids, calcium, and inflammatory cells. These plaques narrow the lumen of the coronary artery, leading to episodic or persistent angina. Atherosclerosis is not just a lipid deposition disease but an inflammatory process with a high-specificity cellular and molecular response. Anti-inflammatory treatment for CHD is a promising therapy; several recent clinical studies (CANTOS, COCOLT, and LoDoCo2) provide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 176 publications
0
4
0
Order By: Relevance
“…Inflammatory response and oxidative stress are important common links. The inflammatory response is activated in both diseases, leading to increased production of inflammatory cytokines ( 52 ). These cytokines include tumor necrosis factor-α (TNF-α) ( 53 ), interleukin-1β (IL-1β) ( 54 ), and interleukin-6 (IL-6) ( 55 ), among others, which are involved in the inflammatory response of the vascular wall and damage to vascular endothelial cells ( 56 ).…”
Section: The Common Relationship Between Dn and Panvascular Diseasementioning
confidence: 99%
“…Inflammatory response and oxidative stress are important common links. The inflammatory response is activated in both diseases, leading to increased production of inflammatory cytokines ( 52 ). These cytokines include tumor necrosis factor-α (TNF-α) ( 53 ), interleukin-1β (IL-1β) ( 54 ), and interleukin-6 (IL-6) ( 55 ), among others, which are involved in the inflammatory response of the vascular wall and damage to vascular endothelial cells ( 56 ).…”
Section: The Common Relationship Between Dn and Panvascular Diseasementioning
confidence: 99%
“…Evidence has accumulated indicating the significant relevance of low-grade inflammatory processes to cardiovascular disease, cancer and vascular risk factors ( 1 , 4 ). Further, high sensitivity C-reactive protein (hs-CRP) is a strong independent predictor of future cardiovascular events ( 3 , 5 ). Cohort studies have shown that elevated CRP is associated with mortality and cardiovascular disease (CVD) events for patients with various CVD locations like coronary artery disease, cerebrovascular disease, peripheral artery disease, and abdominal aortic aneurysm ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic inflammation is associated with the development and progression of many chronic conditions, cardiovascular (CVD), metabolic, renal and oncologic diseases, as well as morbidity and mortality (1)(2)(3). Evidence has accumulated indicating the significant relevance of low-grade inflammatory processes to cardiovascular disease, cancer and vascular risk factors (1,4).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has accumulated indicating the significant relevance of low-grade inflammatory processes to cardiovascular disease, cancer and vascular risk factors ( 4 , 7 ). Further, hs-CRP is a strong independent predictor of future cardiovascular events ( 6 , 8 ). Cohort studies have shown that elevated CRP is associated with mortality and cardiovascular disease (CVD) events for patients with various CVD locations like coronary artery disease, cerebrovascular disease, peripheral artery disease, and abdominal aortic aneurysm ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic inflammation is associated with the development and progression of many chronic conditions like atherosclerosis, diabetes, hypertension, hyperlipidemia, and obesity, as well as morbidity and mortality (4)(5)(6). Figure 1 presents a pathway.…”
Section: Introductionmentioning
confidence: 99%